Basic facts on agrarian reform - Rodriguez, A. G. (Manila Mary Jo Educational Supply, 1992)
Purpose: Reference guide to agrarian reform program in the Philippines.
Content/s: Agrarian Reform (history, constitutional basis administrative machinery). Agrarian Reform Laws. Coordinating Agencies. Program thrusts and constraints. Policy directions and strategies. Republic Acts and Executive Orders.
Keywords: Land reform -- Philippines. -- Law and legislation; Land reform -- Philippines -- Handbook, manuals, etc